Pesantren-Based Economic Empowerment (Case Study of Saifullah An Nahdiyah Pesantren Deli Serdang) - Mufti, Muhammad Ikhsan; Harahap, Muhammad Ikhsan; Imsar, Imsar; Daei, Muhammad Imam (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
Islamic boarding schools have the potential to develop economic independence. To support pesantren-based economic empowerment, a community service was held using the Community Based Research (CBR) method which was carried out at Saifullah An Nahdiyah Namorambe Deli Serdang Islamic boarding school. There are several strategies that can be implemented to realize pesantren-based economic empowerment, namely the Circulation Strategy, Supply-Chain and Economic Integration, Joint Stakeholder Economic Empowerment, Collaboration with Surrounding Communities, Empowerment of Zakat, Infaq, Sadaqah and Waqf Funds. The results of the service show that this activity provides positive value for pesantren managers with a high level of enthusiasm.